The effect of perception of organizational politics on turnover intention: The mediating effect of stress and organizational commitment and moderating effect of honesty - Jang, JinHyeok; Yoo, TaeYong (Korean Journal of Industrial and Organizational Psychology, 2013)
The first purpose of this study was to examine the effect of perception of organizational politics and stress on turnover intention. The second was to examine the mediating effect of stress and organizational commitment in the relationship between perception of organizational politics and turnover intention. The third was to examine the moderating effect of honesty in the relationship between perception of organizational politics and stress. Data were gathered from 203 employees who were working in various organizations in Korea. As results, perception of organizational politics and stress had positive relationship with turnover intention. Stress and organizational commitment sequentially mediated in the relationship between perception of organizational politics and turnover intention. Also, honesty had moderating effect in the relationship between perception of organizational politics and stress because the relationship was more positive when honesty was high than low. Finally, implication of results and limitations and future research tasks were discussed.